MEMBANGUN CITRA RIDWAN DHANI WIRIANATA (RDW) DI INSTAGRAM JELANG KONTESTASI PEMILIHAN WALI KOTA (PILWALKOT) BANDUNG - Diny Fitriawati (KOMUNIKA BANGSA, 2024)
The study looks at how candidate mayor Ridwan Dhani Wirianata uses the instagram social media platform to build an image. Social media, especially instagram, has become an important component as a tool for conducting two-way communication as well as enabling candidate mayors to shape public perception and interact directly with candidate voters. Research results show that Ridwan Dhani Wirianata effectively reinforces his image as a leader close to the community and committed to change by using consistent visual, relevant narrative and two-way interaction with potential voters to help spread the message. Keywords: Candidate Mayor, Images, Instagram